Select the correct answer.
Which statement is true about this equation?

3(-y + 7) = 3(y + 5) + 6

A.
The equation has one solution, y = 0.
B.
The equation has one solution, y = -1.
C.
The equation has no solution.
D.
The equation has infinitely many solutions.

Respuesta :

Answer:

one answer ( y=0 )

Step-by-step explanation:

solve for y

-3y + 21 = 3y + 15 + 6

-3y +21 = 3y +21

(-6y = 0)/-6

y=0

Answer:

A. The equation has one solution, y = 0.

Explanation:

3(-y + 7) = 3(y + 5) + 6

-3y + 21 = 3y + 15 + 6

-3y -3y = 21 - 21

-6y = 0

y = 0